SISTEM TENURIAL TANAH ADAT DI BALI: STUDI TANAH PEKARANGAN DESA DI DESA PAKRAMAN BENG - Ni Putu Arie Sulastri; I G Nyoman Guntur (BHUMI: Jurnal Agraria dan Pertanahan, 2013)
Strictly speaking, the Basic Agrarian Law is not intended to wipe out someone’s or legal body’s rights but ratherto unify the National Land Law. As mentioned at Part II of the Basic Agrarian Law, the conversion had to be done to admit boththe western registered lands and those bearing the adat rights. One of the rights that can be converted into the right ofownership is druwe desa land. Eventhough there has already been a rule on the above conversion, druwe desa at Pakraman BengVillage have not been converted up to the present moment. The concept of Tri Hita Karana is one of the reasons why druwe desastill exists.Keywords: Village yard, druwe desa land, conversion stipulation.